The Effect of Commercial Essential Oil Mixture Applied to Neonatal Simmental Calves on Growth, Development and Health Parameters - Fatma Emir; Bahri Bayram (Turkish Journal of Agriculture: Food Science and Technology)
In this study, the effectiveness of commercial essential oil mixture application in preventing calf losses due to diarrhea and on the growth, development and health parameters of calves was investigated. For this purpose, 24 newborn Simmental calves were used. Following birth, 20 ml of essential oil mixture was given orally via syringe to the calves in the treatment group after drinking milk in the morning for 5 days. The average birth weight of calves was 39.0 ± 0.72 kg. Birth weight of male and female calves were 42.3 ± 1.01 and 38.6 ± 0.96 kg respectively, the difference between groups were found significant. First month weight was 45.7 ± 1.67, 42.4 ± 1.65 kg in the control and treatment groups, respectively. There was no difference between the control and treatment groups in terms of body measurements taken at birth, but a significant difference was observed in chest circumference in favor of the control group in terms of measurements obtained at the 1st month. There was no difference between the treatment and control groups in terms of hematological parameters detected in the blood taken on the 10th day and in the 1-month period. No differences were observed between groups in terms of immunoglobulin levels (IgM and IgG). There was no effect of the commercial essential oil mixture on the fecal score of the calves included in the trial. It was revealed that the essential oil mixture does not make any difference in the growth, development and health of Simmental calves in a one-month period. In future studies on the subject, it is recommended that higher doses of the essential oil mixture be investigated.